(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
The 1992 Maastricht Treaty defined the conditions for the introduction of the euro as a common currency in the European Union. These are macroeconomic indicators that measure the level of nominal convergence achieved and thus the state’s readiness to participate in monetary union. These conditions (convergence criteria) relate to price stability, stability and sustainability of public finances, which includes budget deficits and public debt, exchange rate stability and convergence of long-term interest rates. In addition to nominal convergence, the degree of legal convergence is also assessed - the provisions of national legislation relating to the independence of the central bank, the ban on monetary financing and preferential access to state financing, and integration into the European System of Central Banks are assessed. Among the member states that have not yet adopted the euro, only the Republic of Croatia is fully harmonized in this regard. On July 10, 2020, the Croatian kuna was included in the European Exchange Rate Mechanism (ERM II). Accessing the ERM II mechanism is often referred to as the euro waiting room. Despite the fact that the pandemic caused by the COVID-19 virus has not abated, the Republic of Croatia has not stopped its efforts to become a full member of the euro area. The paper will present the benefits of the introduction of the euro, but also the inevitable costs incurred during the conversion process. As the pandemic has not slowed down the conversion process and the moment of conversion is approaching, on the other hand, there are conflicting views on the introduction of the euro as the official currency, which are trying to be implemented through a referendum. The paper will discuss the legal aspects of Croatia’s accession to the euro area and what measures are envisaged when exchanging the Croatian kuna for the euro, especially from the aspect of consumer protection, given the fact that Croatia has one of the highest euroization rates of all non-euro area EU member states.